Pengaruh Employee Engagement dan Self-Efficacy Terhadap Kinerja Karyawan Universitas Proklamasi 45 - Naufa Setyowati; Faisal Faisal; Andris Wihelmus Dimara (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to determine the effect of Employee Engagement and Self-Efficacy on Employee Performance at Proclamation 45 University. This study uses a survey method on 57 employees. The analysis used in this study is multiple regression analysis. Use a valid value of 0.05. Based on the results of the calculation and analysis of the data used, the multiple regression equation is obtained, namely Y = -0.419 + 0.496X1 + 0.257 Proclamation 45 University. From the findings above, the following conclusions can be drawn. (1) Procrik 45 In higher education, employee engagement has a positive impact on employee performance. This means that good employee engagement will result in better employee performance. (2) Proklik 45 University has a positive influence of self-efficacy on employee performance. This means that if self-efficacy is good, employee performance will be even better. (3) At Proklik 45 University, Employee Engagement and Self-Efficacy have a positive effect on Employee Performance. This means that when employee engagement and self-efficacy are good, employee performance will also be even better. Universitas Proklamasi 45 is expected to continue to strive to improve employee engagement and employee self-efficacy in order to improve employee performance.